2017
DOI: 10.1080/09273948.2017.1294184
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus and the Eye

Abstract: Zika virus (ZIKV), a mosquito-borne flavivirus, is the latest global health concern. Transmission is mainly via Aedes mosquitoes and the infection can be diagnosed on molecular or serologic testings. It typically causes a mild self-remitting illness of low-grade fever, maculopapular rash, and myalgia, but when severe, it is associated with neurological deficits and congenital structural defects. Ocular manifestations are usually mild like nonpurulent conjunctivitis in adults, though it may be linked to uveitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Müller cells, the principal glial cells in the retina, were also found to be permissive to ZIKV and exhibited a proinflammatory response with the activation of many pathways upon infection (S. , which could be partly ameliorated by blocking p38 mitogen-activated protein kinase activation. As with most neurological sequelae, ophthalmic complications appear to be more severe during fetal development (Agrawal et al 2018).…”
Section: Deficits In the Mature Nervous Systemmentioning
confidence: 99%
“…Müller cells, the principal glial cells in the retina, were also found to be permissive to ZIKV and exhibited a proinflammatory response with the activation of many pathways upon infection (S. , which could be partly ameliorated by blocking p38 mitogen-activated protein kinase activation. As with most neurological sequelae, ophthalmic complications appear to be more severe during fetal development (Agrawal et al 2018).…”
Section: Deficits In the Mature Nervous Systemmentioning
confidence: 99%
“…The Zika virus infection was first reported in Uganda, clinically showing a similar presentation to Dengue virus. 51 The disease is mild in adults with acute infection, and includes anterior uveitis with non-purulent conjunctivitis. It has a benign prognosis and is treated with topical steroids.…”
Section: Zika Virus-associated Anterior Uveitismentioning
confidence: 99%
“…It was also found that Sertoli cells of mouse testis were susceptible to ZIKV infection, which implied that ZIKV can be transmitted sexually affecting human male reproductive system [9]. ZIKV also affects the eyes of adults mildly, but significantly in infants with infected mothers [7].…”
Section: Introductionmentioning
confidence: 99%
“…It can be diagnosed via some of the molecular or other serologic testing involving blood, saliva (for neonates) [5], urine [6], etc. The minor infection results in lowgrade fever, myalgia, maculopapular rashes, and in severe cases, adults encounter neurological and congenital structural defects [7]. It may also cause congenital malformations in pregnant woman with fetal and newborn with microcephaly [8].…”
Section: Introductionmentioning
confidence: 99%